Genetic Type and Source Analysis of Natural Gas in the Leikoupo Formation of the Sichuan Basin in China - Qin, Shengfei; Zhang, Benjian; Huang, Chunhu; Li, Jiyuan; Wang, Jiamei; Tao, Gang; Zhou, Zheng (Frontiers in Earth Science, 2022)
The Leikoupo Formation is widely developed in the Sichuan Basin, and commercial gas reservoirs have been discovered in the Leikoupo Formation in western and central Sichuan. Due to the complicated geochemical characteristics of the natural gas in the Leikoupo Formation, there has been considerable divergence over the sources of natural gas in these gas reservoirs over the years, which has affected the evaluation and exploration process of the Leikoupo Formation's gas resources. Aiming at the Leikoupo Formation's natural gas characteristics with substantial heterogeneity and unknown source, this paper selects the Leikoupo Formation gas reservoirs discovered so far in the Zhongba, Yuanba, Longgang, and Moxi gas fields as the research object. In this paper, the genetic type and source of natural gas in the Leikoupo Formation are studied based on natural gas geochemistry combined with the analysis of the geological background. It is believed that part of the gas reservoir at the top of the Leikoupo Formation (T2l4 or T2l3 Members of the Leikoupo Formation) is humic type gas from the source rock of the overlying Xujiahe Formation; part is sapropel gas from the source rock of the Leikoupo Formation itself. The natural gas of T2l1 member in the lower part of Leikoupo Formation is mainly sapropel gas, which comes from the sapropel source rock of the Wujiaping Formation, where the Longtan Formation undergoes a phase change. The reversed of 13C1and 13C2 values in Leikoupo Formation of Yuanba gas field is due to the perfect type of source rock and high degree of evolution.